Accelerated long-term forgetting in aging and intra-sleep awakenings - Mary, Alison; Schreiner, Svenia; Peigneux, Philippe (Frontiers in Psychology, 2013)
The architecture of sleep and the functional neuroanatomical networks subtending memory consolidation processes are both modified with aging, possibly leading to accelerated forgetting in long-term memory. We investigated associative learning and declarative memory consolidation processes in 16 young (18–30 years) and 16 older (65–75 years) healthy adults. Performance was tested using a cued recall procedure at the end of learning (immediate recall), and 30 min and 7 days later. A delayed recognition test was also administered on day 7. Daily sleep diaries were completed during the entire experiment. Results revealed a similar percentage of correct responses at immediate and 30-min recall in young and older participants. However, recall was significantly decreased 7 days later, with an increased forgetting in older participants. Additionally, intra-sleep awakenings were more frequent in older participants than young adults during the seven nights, and were negatively correlated with delayed recall performance on day 7 in the older group. Altogether, our results suggest a decline in verbal declarative memory consolidation processes with aging, eventually leading to accelerated long-term forgetting indicating that increased sleep fragmentation due to more frequent intra-sleep awakenings in older participants contribute to the reported age-related decline in long-term memory retrieval. Our results highlight the sensitivity of long-term forgetting measures to evidence consolidation deficits in healthy aging.